Effects of iron and temperature on Shiga-like toxin I production by Escherichia coli. - Weinstein, D L (1988)
Iron is known to depress Shiga toxin production by Shigella dysenteriae 1, and temperature has been shown to regulate several genes required for Shigella invasiveness. In this study, the influence of iron and temperature on regulation of a highly related toxin, Shiga-like toxin I (SLT-I) of enterohemorrhagic Escherichia coli, was examined in strains lysogenic for the toxin-converting coliphage 933J and in strains carrying the cloned slt-I genes on a high-copy-number plasmid vector. For comparison, S. dysenteriae 1 was included in these studies. As expected, iron suppressed Shiga toxin synthesis, and reduced growth temperature was also found to decrease Shiga toxin production. Iron also suppressed SLT-I synthesis in E. coli lysogenized with phage 933J but did not demonstrably repress toxin synthesis in E. coli strains carrying the cloned slt-I genes. Temperature had no effect on SLT-I synthesis. Mini-Mu lac operon fusions were then isolated in the cloned slt-I genes and used to test for regulation of beta-galactosidase by iron. Iron did not decrease beta-galactosidase production in strains that harbored these operon fusion plasmids. Taken together, these results indicate that iron but not temperature represses SLT-I synthesis when the slt-I genes are phage associated but this suppression is not easily demonstrated when the slt-I genes are cloned on a high-copy-number plasmid.